The Impact of ICT on Economic Sectors - Peter Sasvari (International Journal of Computer Information Systems, 2011)
As the author could not find a reassuring mathematical and statistical method in the literature for studying the effect of information communication technology on enterprises, the author suggested a new research and analysis method that he also used to study the Hungarian economic sectors. The question of what factors have an effect on their net income is vital for enterprises. The highest increment of specific Gross Value Added was produced by the fields of `Manufacturing', `Electricity, gas and water supply', `Transport, storage and communication' and `Financial intermediation'. With the exception of `Electricity, gas and water supply', the other economic sectors belong to the group of underdeveloped branches (below 50%).
Keywords: C10; M15; 330; Information society; Economic sector; Electronic marketplace; ICT